Quality by Design (QbD) Assisted Fabrication of Fast Dissolving Buccal Film for Clonidine Hydrochloride: Exploring the Quality Attributes - Pankaj V. Dangre; Ram D. Phad; Sanjay J. Surana; Shailesh S. Chalikwar (Advances in Polymer Technology)
The present work endeavors fabrication of fast dissolving buccal film of clonidine hydrochloride by employing quality by design (QbD) based approach. The total nine formulations were prepared according to formulation by design helped by JMP software 13.2.1. The patient oriented quality target product profiles were earmarked and on that basis critical quality attributes were identified. Preliminary screening studies along with initial risk assessment eased the selection of film-forming polymer (HPMC E 15) and plasticizer (PEG 400) as CMAs for formulation of films. A 32 full factorial plan was utilized for assurance of impact, i.e., HPMC E15 (X1) and PEG 400 (X2), as independent variables (factors) on thickness (mm) (Y1), disintegration time (s) (Y2), folding endurance (Y3), and tensile strength (kg) (Y4). Furthermore, prediction profiler assists in predicting composition of best formulation encompassing desired targeted response. The optimized formulation (F6) showed fast drug dissolution (>90%) within 8 min, and solid state characterization by DSC, XRD revealed excellent film characteristics. In a nutshell, the fast dissolving buccal film for clonidine hydrochloride was successfully developed assisted by QbD approach with markedly improved biopharmaceutical performance as well as patient compliance.